Effect of Incorporation of Malted Sorghum Flour on Quality of Biscuit - Adhikari, Nischal; Acharya, Dev Raj (Sunsari Technical College Journal, 2016)
Sorghum (S. bicolor) collected from Dhankuta district was used for malting. Sorghum was steeped for 12 hours at Relative humidity of 70±5% and germinated at room temperature (28±3°C) with repeated change of water at interval of every 8 hours for 2, 3,4,5,6 and 7 days. The germinated samples of each day were taken for kilning at the temperature scenario of 50-55°C until moisture reaches to 23%; 70-75°C until moisture reaches to 12%; and 90-95% until moisture reaches to 3-5%. The result of enzyme activity determination showed that the sorghum germinated for 3 days has the higher enzyme activity of 27.39 units per gram dry matter. Proximate analysis of malted and unmalted flour showed significant different (p<0.05) in fat, ash, reducing sugar and crude fiber content. Likewise calcium and iron content of malted flour was significantly increased (p<0.05) than that of unmalted one with subsequent decreased (p<0.05) in their binder oxalate and phytate respectively. The sorghum of higher enzyme activity was then used to prepare the biscuit. Malted sorghum and wheat flour was blended in the following ratios: samples A; 30: 70, sample B; 50:50, sample C; 60:40, sample D; 0:100. The organolaptic test shows the significant difference (p<0.05) between these samples in terms of flavor and test. The mean sensory score was found to be higher for sample C. This suggests that the malted sorghum flour can be used for the preparation of biscuit upto 60% (w/w) of wheat flour without alteration in texture, crispiness, appearance and overall acceptability. Sunsari Technical College Journal 2015, 2(1):33-37